Synaptic transmission as a cooperative phenomenon in confined systems - Chalyi, A.V.; Vasilev, A.N.; Zaitseva, E.V. (Condensed Matter Physics, 2017)
In this review paper, the theory of synaptic transmission (ST) was developed and discussed. We used the hypothesis of isomorphism between: (a) the cooperative behavior of mediators — acetylcholine molecules (ACh)
and cholinoreceptors in a synaptic cleft with binding into mediator-receptor (AChR) complexes, (b) the critical
phenomena in confined binary liquid mixtures. The systems of two (or three) nonlinear differential equations
were proposed to find the change of concentrations of ACh, AChR complexes, and ferment acetylcholinesterase.
The main findings of our study: the linear size of the activation zone was evaluated; the process of postsynaptic
membrane activation was described as a cooperative process; different approximations of ACh synchronous
release were examined; stationary states and types of singular points were studied for the proposed models of
ST; the nonlinear kinetic model with three order parameters demonstrated a strange-attractor behavior. У цьому оглядi була розроблена i обговорена теорiя синаптичної передачi (СП). Ми застосували гiпотезу
iзоморфiзму мiж: (а) кооперативною поведiнкою медiаторiв — молекул ацетилхолiну (ACh) i холiнорецепторiв в синаптичнiй щiлинi з утворенням медiатор-рецепторних (AChR) комплексiв, (б) критичними явищами в просторово обмежених бiнарних рiдких сумiшах. Були запропонованi системи двох (або трьох)
нелiнiйних диференцiальних рiвнянь для опису змiни концентрацiй ACh, комплексiв AChR i ферменту
ацетилхолiнестерази. Основнi результати нашого дослiдження: оцiнено лiнiйний розмiр зони активацiї;
описано процес активацiї постсинаптичної мембрани як кооперативний процес; розглянуто рiзнi апроксимацiйнi функцiї синхронного вивiльнення ACh; дослiджено стацiонарнi стани i типи особливих точок
для запропонованих моделей СП; показано, що нелiнiйна кiнетична модель з трьома параметрами порядку демонструє поведiнку дивного атрактора.